The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ccm.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Treatments

Abstract: Most viral respiratory tract infections are caused by classic respiratory viruses, including influenza, respiratory syncytial virus, human metapneumovirus, parainfluenza, rhinovirus, and adenovirus, whereas other viruses, such as herpes simplex, cytomegalovirus, and measles virus, can opportunistically affect the respiratory tract. The M2 inhibitors, amantadine and rimantadine, were historically effective for the prevention and treatment of influenza A but all circulating strains are currently resistant to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 115 publications
0
50
0
Order By: Relevance
“…The NA inhibitors are the only virus protein-specific antivirals currently available for control of influenza virus infections worldwide. 17 Overreliance upon NA inhibitors increases the risk of antiviral resistance and justifies the pursuit of novel inhibitors that target different viral and/or host targets. Here, we demonstrated that enisamium inhibits replication of multiple subtypes of influenza A and B viruses in dNHBE cells.…”
Section: Discussionmentioning
confidence: 99%
“…The NA inhibitors are the only virus protein-specific antivirals currently available for control of influenza virus infections worldwide. 17 Overreliance upon NA inhibitors increases the risk of antiviral resistance and justifies the pursuit of novel inhibitors that target different viral and/or host targets. Here, we demonstrated that enisamium inhibits replication of multiple subtypes of influenza A and B viruses in dNHBE cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is no vaccine for HRSV [8] and there is still a need for safe and effective treatments [9,10]. There is only one Food and Drug Administration approved prophylaxis, palivizumab, a humanized monoclonal antibody against the HRSV fusion (F) glycoprotein [11], and one therapeutic treatment, ribavirin [12], a nucleoside analogue with unclear efficacy or exact mechanism of action in HRSVinfected patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Potent vacuolar ATPase (V-ATPase) inhibitors, namely diphyllin and bafilomycin, previously shown to have broad-spectrum antiviral activity represent another possibility against influenza virus infection [58][59][60]. Briefly, the antiviral mechanism of amantadine is based on nterference with the viral protein, M2 (an ion channel), the protein needed for the viral particle to become uncoated once it is taken inside the cell by endocytosis [61]. Also, oseltamivir carboxylate mechanism implies a selective inhibition of influenza virus neuraminidase enzymes, which are glycoproteins found on the virion surface, very important for viral entry into uninfected cells, for the release of recently formed virus particles from infected cells, and for the further spread of the infectious virus in the body [62,63].…”
Section: Antiviral Agents Used In Nanotechnologymentioning
confidence: 99%